Toward Sustainable Development: Micro-Level Explorations in Management Research - Hollands, Lisa (Universität Vechta, 2023)
The pursuit of sustainable development is a pressing challenge for today’s global society. Despite broad academic consensus on the need to transition towards more sustainable and resilient pathways, in practice shortcomings in the implementation and management of sustainability remain. The scientific discourse on sustainability management extends over various domains and perspectives, with a predominant focus on the macro- and meso-level of analysis. In contrast the micro-level literature on sustainability management is comparatively limited but growing, with the potential to deepen and broaden the understanding of sustainability. Within the micro-level research stream, scholars have pointed to promising avenues such as emphasizing more social elements and well-being, taking a glance across borders, exploiting the methodological toolbox and leveling up while investigating the micro-level. Collectively, the four articles advance on these avenues and address a wide range of sustainability management questions, contexts and stakeholders. In doing so, the present dissertation aims to contribute to a more comprehensive understanding of the complexities of sustainability phenomena through a socio-psychological lens and a focus on the individual.
Keywords: Management Research; Sustainable Development; Micro-Level Research; Sustainability; Sozialwissenschaften::330 Wirtschaft; Philosophie und Psychologie::150 Psychologie